TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP KENAIKAN IURAN BPJS KESEHATAN DI MASA PANDEMI COVID 19 BERDASARKAN PERATURAN PRESIDEN NOMOR 64 TENTANG JAMINAN KESEHATAN - Boby, Muhammad; Yazwardi, Yazwardi; Lubis, Ramiah (Muamalah, 2021)
ABSTRACT This research is entitled A Gradual Sharia Economic Law Review RegulatingTariff Increase for BPJS Health Participants Based on Presidential Regulation Number 64of 2020 concerning Health Insurance, there are several reasons for the increase in BPJScontributions. First, one of the main causes of the deficit in the National Health Insurance(JKN) program that has occurred since the beginning of its implementation is the amountof contributions that are underpriced and adverse for independent participants. So that thedeficit increases from year to year. Second, many independent participants only registerwhen they are sick and require expensive medical costs. After recovering, participants stoppaying dues or are not disciplined when paying dues. There are two things that become thefocal point of this research, namely, first, how to increase the rates for BPJS Kesehatanparticipants based on Presidential Regulation Number 64 of 2020 concerning HealthInsurance, secondly, how is the Sharia Economic Law Review of the Increase in Tariffs forBPJS Kesehatan Participants Based on Presidential Regulation Number 64 of 2020 AboutHealth Insurance. The methodology used in this research through anapproach is empirical shown toget things that are direct and library researchlibrary research () to get things that aretheoretical. The data sources used consisted of two, namely primary data and secondarydata. The results of this study concluded that (1) the increase in BPJS Healthcontributions during the Covid 19 pandemic which reached 100% was deemedincompatible with the increase in the UMP every year of only 8.5%, this increase was alsonot in accordance with the principles of syaraih economics and was against Pancasila. 5"Social justice for all Indonesian people" it can be concluded that this increase incontributions is not in accordance with Sharia Economic Law Key words: BPJS Health, Sharia Economic Law, Presidential Regulation Number 64of 2020 concerning Health Insurance